2.2.29 Problems 2801 to 2900

Table 2.59: Main lookup table. Sorted sequentially by problem number.

#

ODE

CAS classification

Solved?

time (sec)

2801

\[ {}\left [\begin {array}{c} x^{\prime }=-5 x+3 y \\ y^{\prime }=y-x \end {array}\right ] \]

system_of_ODEs

0.608

2802

\[ {}\left [\begin {array}{c} x^{\prime }=x-4 y \\ y^{\prime }=4 x-7 y \end {array}\right ] \]

system_of_ODEs

0.389

2803

\[ {}\left [\begin {array}{c} x^{\prime }=-7 x+y-6 z \\ y^{\prime }=10 x-4 y+12 z \\ z^{\prime }=2 x-y+z \end {array}\right ] \]

system_of_ODEs

0.507

2804

\[ {}\left [\begin {array}{c} x^{\prime }=3 x+2 y+4 z \\ y^{\prime }=2 x+2 z \\ z^{\prime }=4 x+2 y+3 z \end {array}\right ] \]

system_of_ODEs

0.437

2805

\[ {}\left [\begin {array}{c} x^{\prime }=2 y+z \\ y^{\prime }=-x-3 y-z \\ z^{\prime }=x+y-z \end {array}\right ] \]

system_of_ODEs

0.437

2806

\[ {}\left [\begin {array}{c} x^{\prime }=-2 x+y+z \\ y^{\prime }=-3 x+2 y+3 z \\ z^{\prime }=x-y-2 z \end {array}\right ] \]

system_of_ODEs

0.336

2807

\[ {}\left [\begin {array}{c} x^{\prime }=2 y \\ y^{\prime }=-2 x \\ z^{\prime }=2 h \\ h^{\prime }=-2 z \end {array}\right ] \]

system_of_ODEs

0.549

2808

\[ {}\left [\begin {array}{c} x^{\prime }=2 y+z \\ y^{\prime }=-2 x+h \\ z^{\prime }=2 h \\ h^{\prime }=-2 z \end {array}\right ] \]

system_of_ODEs

0.566

2809

\[ {}x^{\prime } = x \left (1-x\right ) \]

[_quadrature]

1.883

2810

\[ {}x^{\prime } = -x \left (1-x\right ) \]

[_quadrature]

1.750

2811

\[ {}x^{\prime } = x^{2} \]

[_quadrature]

1.278

2812

\[ {}\left [\begin {array}{c} x_{1}^{\prime }=x_{2} \\ x_{2}^{\prime }=-\frac {\left (x_{1}^{2}+\sqrt {x_{1}^{2}+4 x_{2}^{2}}\right ) x_{1}}{2} \end {array}\right ] \]

system_of_ODEs

0.067

2813

\[ {}\left [\begin {array}{c} x_{1}^{\prime }=-x_{1}-x_{2}+1 \\ x_{2}^{\prime }=2 x_{1}-x_{2}+5 \end {array}\right ] \]

system_of_ODEs

0.891

2814

\[ {}\left [\begin {array}{c} x^{\prime }=x-x^{3}-x y \\ y^{\prime }=2 y-y^{5}-y \,x^{4} \end {array}\right ] \]

system_of_ODEs

0.069

2815

\[ {}\left [\begin {array}{c} x^{\prime }=x^{2}+y^{2}+1 \\ y^{\prime }=x^{2}-y^{2} \end {array}\right ] \]

system_of_ODEs

0.064

2816

\[ {}\left [\begin {array}{c} x^{\prime }=x^{2}+y^{2}-1 \\ y^{\prime }=2 x y \end {array}\right ] \]

system_of_ODEs

0.054

2817

\[ {}\left [\begin {array}{c} x^{\prime }=6 x-6 x^{2}-2 x y \\ y^{\prime }=4 y-4 y^{2}-2 x y \end {array}\right ] \]

system_of_ODEs

0.059

2818

\[ {}\left [\begin {array}{c} x^{\prime }=\tan \left (x+y\right ) \\ y^{\prime }=x+x^{3} \end {array}\right ] \]

system_of_ODEs

0.036

2819

\[ {}\left [\begin {array}{c} x^{\prime }={\mathrm e}^{y}-x \\ y^{\prime }={\mathrm e}^{x}+y \end {array}\right ] \]

system_of_ODEs

0.054

2820

\[ {}z^{\prime \prime }+z^{3} = 0 \]

[[_2nd_order, _missing_x], [_2nd_order, _reducible, _mu_x_y1]]

1.617

2821

\[ {}z^{\prime \prime }+z+z^{5} = 0 \]

[[_2nd_order, _missing_x], [_2nd_order, _reducible, _mu_x_y1]]

278.431

2822

\[ {}z^{\prime \prime }+{\mathrm e}^{z^{2}} = 1 \]

[[_2nd_order, _missing_x], [_2nd_order, _reducible, _mu_x_y1]]

1.036

2823

\[ {}z^{\prime \prime }+\frac {z}{1+z^{2}} = 0 \]

[[_2nd_order, _missing_x], [_2nd_order, _reducible, _mu_x_y1]]

1.191

2824

\[ {}z^{\prime \prime }+z-2 z^{3} = 0 \]

[[_2nd_order, _missing_x], _Duffing, [_2nd_order, _reducible, _mu_x_y1]]

2.250

2825

\[ {}\left [\begin {array}{c} x_{1}^{\prime }=-5 x_{1}+x_{2} \\ x_{2}^{\prime }=x_{1}-5 x_{2} \end {array}\right ] \]

system_of_ODEs

0.421

2826

\[ {}\left [\begin {array}{c} x_{1}^{\prime }=-x_{2} \\ x_{2}^{\prime }=8 x_{1}-6 x_{2} \end {array}\right ] \]

system_of_ODEs

0.428

2827

\[ {}\left [\begin {array}{c} x_{1}^{\prime }=4 x_{1}-x_{2} \\ x_{2}^{\prime }=-2 x_{1}+5 x_{2} \end {array}\right ] \]

system_of_ODEs

0.421

2828

\[ {}\left [\begin {array}{c} x_{1}^{\prime }=-4 x_{1}-x_{2} \\ x_{2}^{\prime }=x_{1}-6 x_{2} \end {array}\right ] \]

system_of_ODEs

0.377

2829

\[ {}\left [\begin {array}{c} x_{1}^{\prime }=x_{1}-4 x_{2} \\ x_{2}^{\prime }=-8 x_{1}+4 x_{2} \end {array}\right ] \]

system_of_ODEs

0.623

2830

\[ {}\left [\begin {array}{c} x_{1}^{\prime }=3 x_{1}-x_{2} \\ x_{2}^{\prime }=5 x_{1}-3 x_{2} \end {array}\right ] \]

system_of_ODEs

0.421

2831

\[ {}\left [\begin {array}{c} x_{1}^{\prime }=2 x_{2} \\ x_{2}^{\prime }=-2 x_{1}-x_{2} \end {array}\right ] \]

system_of_ODEs

0.719

2832

\[ {}\left [\begin {array}{c} x_{1}^{\prime }=x_{1}-x_{2} \\ x_{2}^{\prime }=5 x_{1}-3 x_{2} \end {array}\right ] \]

system_of_ODEs

0.493

2833

\[ {}\left [\begin {array}{c} x_{1}^{\prime }=2 x_{1}+x_{2} \\ x_{2}^{\prime }=-5 x_{1}-2 x_{2} \end {array}\right ] \]

system_of_ODEs

0.475

2834

\[ {}\left [\begin {array}{c} x_{1}^{\prime }=4 x_{2} \\ x_{2}^{\prime }=-9 x_{1} \end {array}\right ] \]

system_of_ODEs

0.460

2835

\[ {}y^{\prime \prime }+\lambda y = 0 \]
i.c.

[[_2nd_order, _missing_x]]

3.059

2836

\[ {}y^{\prime \prime }+\lambda y = 0 \]
i.c.

[[_2nd_order, _missing_x]]

3.171

2837

\[ {}y^{\prime \prime }-\lambda y = 0 \]
i.c.

[[_2nd_order, _missing_x]]

3.777

2838

\[ {}y^{\prime \prime }+\lambda y = 0 \]
i.c.

[[_2nd_order, _missing_x]]

3.074

2839

\[ {}y^{\prime \prime }-2 y^{\prime }+\left (1+\lambda \right ) y = 0 \]
i.c.

[[_2nd_order, _missing_x]]

2.869

2840

\[ {}y^{\prime \prime }+\lambda y = 0 \]
i.c.

[[_2nd_order, _missing_x]]

3.027

2841

\[ {}x y+\left (x^{2}+1\right ) y^{\prime } = 0 \]

[_separable]

1.730

2842

\[ {}x y^{2}+x +\left (y-x^{2} y\right ) y^{\prime } = 0 \]

[_separable]

3.601

2843

\[ {}1+y^{2}+\left (x^{2}+1\right ) y^{\prime } = 0 \]

[_separable]

2.128

2844

\[ {}y+y^{\prime } x = 0 \]

[_separable]

2.115

2845

\[ {}y^{\prime } = 2 x y \]

[_separable]

1.628

2846

\[ {}x y^{2}+x +\left (x^{2} y-y\right ) y^{\prime } = 0 \]

[_separable]

2.027

2847

\[ {}\sqrt {-x^{2}+1}+\sqrt {1-y^{2}}\, y^{\prime } = 0 \]

[_separable]

2.000

2848

\[ {}\left (x +1\right ) y^{\prime }-1+y = 0 \]

[_separable]

1.822

2849

\[ {}y^{\prime } \tan \left (x \right )-y = 1 \]

[_separable]

1.824

2850

\[ {}y+3+\cot \left (x \right ) y^{\prime } = 0 \]

[_separable]

1.964

2851

\[ {}y^{\prime } = \frac {x}{y} \]

[_separable]

3.563

2852

\[ {}x^{\prime } = 1-\sin \left (2 t \right ) \]

[_quadrature]

0.557

2853

\[ {}y+y^{\prime } x = y^{2} \]

[_separable]

2.064

2854

\[ {}\sin \left (x \right ) \cos \left (y\right )^{2}+\cos \left (x \right )^{2} y^{\prime } = 0 \]

[_separable]

3.564

2855

\[ {}\sec \left (x \right ) \cos \left (y\right )^{2} = \cos \left (x \right ) \sin \left (y\right ) y^{\prime } \]

[_separable]

8.467

2856

\[ {}y+y^{\prime } x = x y \left (y^{\prime }-1\right ) \]

[_separable]

1.433

2857

\[ {}x y+\sqrt {x^{2}+1}\, y^{\prime } = 0 \]

[_separable]

1.984

2858

\[ {}y = x y+x^{2} y^{\prime } \]

[_separable]

1.847

2859

\[ {}\tan \left (x \right ) \sin \left (x \right )^{2}+\cos \left (x \right )^{2} \cot \left (y\right ) y^{\prime } = 0 \]

[_separable]

5.505

2860

\[ {}y^{2}+y y^{\prime }+x^{2} y y^{\prime }-1 = 0 \]

[_separable]

3.986

2861

\[ {}y^{\prime } = \frac {y}{x} \]
i.c.

[_separable]

1.919

2862

\[ {}y^{\prime } x +2 y = 0 \]
i.c.

[_separable]

2.703

2863

\[ {}\sin \left (x \right ) \cos \left (y\right )+\cos \left (x \right ) \sin \left (y\right ) y^{\prime } = 0 \]
i.c.

[_separable]

3.167

2864

\[ {}x^{2} y^{\prime }+y^{2} = 0 \]
i.c.

[_separable]

3.629

2865

\[ {}y^{\prime } = {\mathrm e}^{y} \]
i.c.

[_quadrature]

1.611

2866

\[ {}{\mathrm e}^{y} \left (y^{\prime }+1\right ) = 1 \]
i.c.

[_quadrature]

1.989

2867

\[ {}1+y^{2} = \frac {y^{\prime }}{x^{3} \left (x -1\right )} \]
i.c.

[_separable]

3.259

2868

\[ {}x^{2}+3 y^{\prime } x = y^{3}+2 y \]
i.c.

[_rational, _Abel]

14.246

2869

\[ {}\left (x^{2}+x +1\right ) y^{\prime } = y^{2}+2 y+5 \]
i.c.

[_separable]

4.858

2870

\[ {}\left (x^{2}-2 x -8\right ) y^{\prime } = y^{2}+y-2 \]
i.c.

[_separable]

4.393

2871

\[ {}x +y = y^{\prime } x \]

[_linear]

1.481

2872

\[ {}\left (x +y\right ) y^{\prime }+x = y \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

3.618

2873

\[ {}y^{\prime } x -y = \sqrt {x y} \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

7.696

2874

\[ {}y^{\prime } = \frac {2 x -y}{x +4 y} \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

4.588

2875

\[ {}y^{\prime } x -y = \sqrt {x^{2}-y^{2}} \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

54.954

2876

\[ {}x +y y^{\prime } = 2 y \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.290

2877

\[ {}y^{\prime } x -y+\sqrt {y^{2}-x^{2}} = 0 \]

[[_homogeneous, ‘class A‘], _dAlembert]

3.442

2878

\[ {}x^{2}+y^{2} = x y y^{\prime } \]

[[_homogeneous, ‘class A‘], _rational, _Bernoulli]

5.477

2879

\[ {}\left (x y-x^{2}\right ) y^{\prime }-y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

37.523

2880

\[ {}y+y^{\prime } x = 2 \sqrt {x y} \]

[[_homogeneous, ‘class A‘], _dAlembert]

9.002

2881

\[ {}x +y+\left (x -y\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

4.676

2882

\[ {}y \left (x^{2}-x y+y^{2}\right )+x y^{\prime } \left (x^{2}+x y+y^{2}\right ) = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

53.445

2883

\[ {}y^{\prime } x -y-x \sin \left (\frac {y}{x}\right ) = 0 \]

[[_homogeneous, ‘class A‘], _dAlembert]

3.814

2884

\[ {}y^{\prime } = \frac {y}{x}+\cosh \left (\frac {y}{x}\right ) \]

[[_homogeneous, ‘class A‘], _dAlembert]

5.115

2885

\[ {}x^{2}+y^{2} = 2 x y y^{\prime } \]
i.c.

[[_homogeneous, ‘class A‘], _rational, _Bernoulli]

9.719

2886

\[ {}\left (\frac {x}{y}+\frac {y}{x}\right ) y^{\prime }+1 = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

5.609

2887

\[ {}x \,{\mathrm e}^{\frac {y}{x}}+y = y^{\prime } x \]
i.c.

[[_homogeneous, ‘class A‘], _dAlembert]

4.514

2888

\[ {}y^{\prime } = \frac {x +y}{x -y} \]
i.c.

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

5.581

2889

\[ {}y^{\prime } = \frac {y}{x}+\tan \left (\frac {y}{x}\right ) \]
i.c.

[[_homogeneous, ‘class A‘], _dAlembert]

5.701

2890

\[ {}\left (3 x y-2 x^{2}\right ) y^{\prime } = 2 y^{2}-x y \]
i.c.

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

47.150

2891

\[ {}y^{\prime } = \frac {y}{x -k \sqrt {x^{2}+y^{2}}} \]

[[_homogeneous, ‘class A‘], _dAlembert]

78.126

2892

\[ {}y^{2} \left (y y^{\prime }-x \right )+x^{3} = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

15.394

2893

\[ {}y^{\prime } = \frac {y}{x}+\tanh \left (\frac {y}{x}\right ) \]

[[_homogeneous, ‘class A‘], _dAlembert]

7.265

2894

\[ {}x +y-\left (x -y+2\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.434

2895

\[ {}x +\left (x -2 y+2\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class C‘], _dAlembert]

4.199

2896

\[ {}2 x -y+1+\left (x +y\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

4.615

2897

\[ {}x -y+2+\left (x +y-1\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.601

2898

\[ {}x -y+\left (y-x +1\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.013

2899

\[ {}y^{\prime } = \frac {x +y-1}{x -y-1} \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.443

2900

\[ {}x +y+\left (2 x +2 y-1\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.747